Prenatal Alcohol Exposure in Relation to Autism Spectrum Disorder: Findings from the Study to Explore Early Development (SEED). Issue 6 (7th September 2017) - Singer, Alison B.; Aylsworth, Arthur S.; Cordero, Christina; Croen, Lisa A.; DiGuiseppi, Carolyn; Fallin, M. Daniele; Herring, Amy H.; Hooper, Stephen R.; Pretzel, Rebecca E.; Schieve, Laura A.; Windham, Gayle C.; Daniels, Julie L.
Abstract: Background: Prenatal alcohol exposure can affect neurodevelopment, but few studies have examined associations with autism spectrum disorder (ASD). Methods: We assessed the association between maternal alcohol use and ASD in the Study to Explore Early Development, a multi‐site case–control study of children born between September 2003 and August 2006 in the US Regression analyses included 684 children with research clinician‐confirmed ASD, 869 children with non‐ASD developmental delays or disorders (DDs), and 962 controls ascertained from the general population (POP). Maternal alcohol exposure during each month from 3 months prior to conception until delivery was assessed by self‐report. Results: Mothers of POP children were more likely to report any prenatal alcohol use than mothers of children with ASD or DD. In trimester one, 21.2% of mothers of POP children reported alcohol use compared with 18.1% and 18.2% of mothers of children with ASD or DD, respectively (adjusted OR for ASD vs. POP 0.8, 95% confidence interval 0.6, 1.1). During preconception and the first month of pregnancy, one to two drinks on average per week was inversely associated with ASD risk. Conclusions: These results do not support an adverse association between low‐level alcohol exposure and ASD, although these findings were based on retrospective self‐reported alcohol use. Unmeasured confounding or exposure misclassification may explain inverse associations with one to two drinks per week. Pregnant or potentially pregnant women should continue to follow recommendations to avoid alcohol use because of other known effects on infant health and neurodevelopment.